2014
DOI: 10.1021/ma500762x
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Rubbing: A Versatile Method to Align π-Conjugated Polymers without Alignment Substrate

Abstract: Mechanical rubbing of polymer films has been widely used in the liquid crystal display industry to prepare oriented alignment layers of polyimides. We show that this fast orientation method can be successfully applied to a large palette of different π-conjugated systems, i.e., p-and n-type semiconducting homopolymers and alternating copolymers. Transmission electron microscopy, grazing incidence X-ray diffraction and UV−vis absorption spectroscopy reveal that both, the temperature of the films during rubbing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
150
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(164 citation statements)
references
References 37 publications
8
150
0
Order By: Relevance
“…It is a well-known technique applied in the field of LCDs. 2D-XRD measurements revealed that rubbing P3HT layers generates molecular order whether the films are rubbed with velvet or nylon materials ( Figure 15) [33,[65][66][67][68]. In particular, depending on the temperature at which the rubbing process is performed, the amount of face-on and edge-on crystallites can be controlled to induce the adequate crystallite orientation depending on the application [66].…”
Section: Molecular Orientation By Postdeposition Mechanical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a well-known technique applied in the field of LCDs. 2D-XRD measurements revealed that rubbing P3HT layers generates molecular order whether the films are rubbed with velvet or nylon materials ( Figure 15) [33,[65][66][67][68]. In particular, depending on the temperature at which the rubbing process is performed, the amount of face-on and edge-on crystallites can be controlled to induce the adequate crystallite orientation depending on the application [66].…”
Section: Molecular Orientation By Postdeposition Mechanical Processesmentioning
confidence: 99%
“…In particular, depending on the temperature at which the rubbing process is performed, the amount of face-on and edge-on crystallites can be controlled to induce the adequate crystallite orientation depending on the application [66]. For instance, the vertical hole mobility can be enhanced about twofold with the generation of face-on crystallites and mobility anisotropy can also be generated through rubbing [65][66][67]. Although most of the studies on rubbing focus on P3HT, this process is not limited to thiophene-based polymers.…”
Section: Molecular Orientation By Postdeposition Mechanical Processesmentioning
confidence: 99%
“…However, not only the chemical structure of organic materials but also molecular alignment within the thin film strongly influence device properties . Varying the molecular ordering, we can change the ionization potential, light absorption and luminescence, and increase carrier mobility and stability of the films . From this point, the main objective upon device fabrication is to achieve the definite control of molecular alignment in the thin films.…”
Section: Objectives and Backgroundmentioning
confidence: 99%
“…1,4,5 Varying the molecular ordering, we can change the ionization potential, 6 light absorption and luminescence, and increase carrier mobility and stability of the films. 5,[7][8][9] From this point, the main objective upon device fabrication is to achieve the definite control of molecular alignment in the thin films. There is a number of methods to align molecules: mechanical orientation, LB films deposition, self-organization of liquid crystal (LC) materials, deposition on specific alignment surfaces, 5,10 and so on.…”
mentioning
confidence: 99%
“…Large‐area alignment can be achieved using casting techniques such as directional solidification, solution shearing, and microchannel confinement, yielding anisotropic, and in some cases substantially improved, carrier mobilities . Mechanical post‐processing techniques such as stamping, rubbing, and straining have also been shown to induce polymer chains to adopt highly aligned configurations . Molecular design of polymers exhibiting liquid crystalline behavior has also been used to supplement the effectiveness of alignment techniques …”
Section: Introductionmentioning
confidence: 99%